Khan Academy Platform and Mathematics education: what the research says (Research, Society and Development, 2020)
The present work consists of surveying research related to the Khan Academy platform and its use in the area of Education. CAPES, SciELO, Google Scholar and Google databases were used as a search tool. Ten works were selected, using state of the art methodology and categorical analysis for data treatment. Half of the works present elements that point to benefits not only for students, but also for teachers. Among the results of the researches analyzed, there is unanimity that the use of technological didactic resources favors teaching and, therefore, the learning process. However, there are counterpoints that cover the content approach on the platform, as well as the need for time and planning so that the teacher can explore and personify teaching.